Kajian 14 Pillar Pada Travel and Tourism Competitiveness Index (TTCI) Sebagai Indikator Daya Saing Pariwisata Suatu Negara - Yuviani Kusumawardhani (Tourism Scientific Journal, 2020)
The concept of competitiveness is undergoing a revolution. The revolution of competitiveness theory becomes a new paradigm. Initially, competitiveness theory discusses the ability of a company to survive in a dynamic market. The new paradigm regarding the theory of competitiveness that has become normal science is currently being defined as a concept of competitiveness between countries. One of the competitiveness of a country can be obtained from the tourism sector. Why tourism? Because tourism has developed into a major and mainstay industry in the world. The World Economic Forum (WEF) as an international institution issued a report measuring the travel and tourism competitiveness of its 136 member countries. The report in question is better known as the Travel and Tourism Competitiveness Index (TTCI), in which there are 14 pillars that are indicators of a country's competitiveness. This study uses a qualitative approach with a literature study method, which aims to examine the 14 pillars as an indicator of the competitiveness of a country's tourism. These indicators are actually quite good in describing the competitiveness of a country in travel and tourism, but in developing countries there are several indicators that are still difficult to achieve because development in certain sectors is still in the process of development and takes a long time to be assessed to reach the minimum value of the TTCI indicator. This has an impact on the assessment based on indicators on TTCI for developing countries that is not optimal.